2014
DOI: 10.1016/j.bbacli.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Low zinc levels is associated with increased inflammatory activity but not with atherosclerosis, arteriosclerosis or endothelial dysfunction among the very elderly

Abstract: BackgroundReduced zinc intake has been related to atherogenesis and arteriosclerosis. We verified this assumption in very old individuals, which are particularly prone to both zinc deficiency and structural and functional changes in the arterial wall.MethodsSubjects (n = 201, 80–102 years) with uneventful cardiovascular history and who were not in use of anti-inflammatory treatments in the last 30-days were enrolled. Daily intake of zinc, lipid profile, plasma C-reactive protein (CRP), plasma zinc, flow-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Children with leukocytosis were excluded due to the inverse association of serum zinc with inflammation. 19 At first glance, the observation of hypoferritinemia in the zinc-deficient child with the lowest Hb in the whole group, and the low ferritin in the child with the lowest Hb in the control group, could suggest that anemia is secondary to decreased ferritin. Statistical analysis of the whole group, however, supported the reverse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with leukocytosis were excluded due to the inverse association of serum zinc with inflammation. 19 At first glance, the observation of hypoferritinemia in the zinc-deficient child with the lowest Hb in the whole group, and the low ferritin in the child with the lowest Hb in the control group, could suggest that anemia is secondary to decreased ferritin. Statistical analysis of the whole group, however, supported the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…We measured non‐fasting levels of all parameters in order to ensure consistency. Children with leukocytosis were excluded due to the inverse association of serum zinc with inflammation …”
Section: Discussionmentioning
confidence: 99%
“…In Qi et al study, opposite direction about role of zinc was concluded that can lead to protective or harmful result [ 11 ]. The De Paula et al study expressed that enormous and transient zinc accumulation during cerebral ischemia was significantly involved in brain damage through promotion of neuronal apoptotic death, so removing zinc can be a means of reducing ischemic brain injury [ 14 ]. Tomas-Sanchez et al found that despite the neuroprotective role of lower doses of zinc against cerebral ischemia, zinc accumulation leads to cytotoxicity, neuroinflammation, neuronal death, and cerebral dysfunction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The colorimetric method had been used for the determination of zinc levels in 560 nm. Serum level of zinc was defined as 70–120 μ g/dl and lower than 70 μ g/dl was considered a zinc deficiency while levels above 120 μ g/dl were considered increased zinc level [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, high levels of A2M in NMR may be important to maintain zinc homeostasis [ 51 ]. In this line it is important to know that mainly elderly people suffer from a zinc deficiency, which comes along with an immune deficiency and other age-related diseases [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%